An atypical location for Malignant Triton Tumor – a case report - Baía, Catarina; Martins, Pedro; Serralva, Mário; Pinto, Paula; Marques, Mariana; Silva, José Carlos; Cardoso, Maria João; Costa, João; Afonso, Mariana; Videira, José Flávio; Moreira, Augusto; Sousa, Joaquim Abreu de (Brazilian Journal of Case Reports, 2023)
The authors report a case of a 52-years-old female patient, without personal or family history of genetic diseases, referred to our institution after an atypical gastrectomy with R2 resection for a gastric tumor suspected to be a GIST. Histopathological review was performed and a diagnosis of a high-grade soft tissue neoplasm with rhabdomyoblastic differentiation, compatible with malignant Triton tumor was rendered. After excluding residual disease, the patient was proposed to adjuvant chemotherapy. Two months later, a follow-up CT-scan showed a local recurrence, with no metastatic spread. After multidisciplinary team decision, she was submitted to R0 resection of the tumor consisting on total gastrectomy and splenectomy. Histopathological examination confirmed the recurrence of the malignant Triton tumor of gastric wall, with free margins. The patient was proposed for surveillance and currently there is no evidence of recurrent disease after 18-months. This case highlights the importance of referral to a specialized sarcoma center in order to achieve a precise preoperative diagnosis and then a R0 resection. In our case, an R0 resection has resulted in the absence of disease recurrence during the 18-month. Furthermore, to the best of our knowledge, no malignant Triton tumor arising in the stomach has been published so far.